PENGARUH TINGKAT PENDIDIKAN TERHADAP PENGETAHUAN PENGGUNAAN ANTASIDA DI DUSUN KEPEK BANTULPERIODE JANUARI 2022 - Ajeng Eka Septyaningrum; Dwi Hastuti (Universitas Haji Sumatera Utara, 2022)
Gastritis is an inflammation of the stomach wall. Based on data from the Bantul Health Office, the incidence of gastritis in 2020 was in the third position of the 10 largest diseases in the Bantul District Health Center with a total of 25,517 cases. One treatment that can be done is to use antacids. The purpose of this study was to determine the effect of education level on knowledge of antacid use in Kepek Village, Bantul for the period January 2022. This type of research is using analytical observational method with a cross sectional approach and data collection by giving questionnaires to the respondents. The sample used was 95 respondents. The research instrument used was a questionnaire sheet. Data analysis was done inferentially. The number of correct answers is calculated then calculates the percentage level of knowledge and is categorized based on good, enough and less. The effect of education level on knowledge of antacid use was tested using SPSS with Chi-Square test. The results of data processing show that the education level of the people of Dusun Kepek consists of elementary school (12.63%), junior high school (14.74%), high school (54.73%) and undergraduate (17.89%). Validation test was carried out on 18 questions and obtained valid results totaling 13 questions. Based on the Chi-Square Test, a significance value of 0.001 <0.05 Ha was accepted, meaning that there was an influence between education level on knowledge of antacid use in Kepek Village, Bantul.